Proceedings 22nd International Conference on Distributed Computing Systems Workshops
DOI: 10.1109/icdcsw.2002.1030807
|View full text |Cite
|
Sign up to set email alerts
|

Managing interaction concerns in Web-service systems

Abstract: Web services dramatically increase the reach of ebusiness. A homogeneous model that spans internal as well as external resources enables uniform solutions to complex business problems. Yet, the complexity of webservice-based systems increases exponentially with their scope. Separation of crosscutting concerns and active management of aspects are fundamental in web-servicebased solutions.In this paper, we first introduce web services and the concept of business interaction concerns. We then propose a process-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…In other words, this is not a generic framework that can be used to improve the design of the process models, but rather execute already known alternative processes after detecting pre-defined situations. Composing and swapping services based on QoS, cost, rules, and in the event of failure [27] [24] [32] [34] Extracting roles and crosscutting concerns from composite services [37] Customizing process instances based on user profiles or SLAs [9] Adapting service composition and collaboration policies [5] [36] Using monitoring aspects to detect undesired situations Furthermore in [1], Algahtani and Zedan aim to solve several problems with service-based technologies using a combination of an event-driven architecture and aspect-oriented methods. The targeted problems are the lack of design-time adaptability, lack of testability for composition correctness, lack of behavioral features, and lack of runtime adaptability.…”
Section: A Aspect-oriented Methodsmentioning
confidence: 99%
“…In other words, this is not a generic framework that can be used to improve the design of the process models, but rather execute already known alternative processes after detecting pre-defined situations. Composing and swapping services based on QoS, cost, rules, and in the event of failure [27] [24] [32] [34] Extracting roles and crosscutting concerns from composite services [37] Customizing process instances based on user profiles or SLAs [9] Adapting service composition and collaboration policies [5] [36] Using monitoring aspects to detect undesired situations Furthermore in [1], Algahtani and Zedan aim to solve several problems with service-based technologies using a combination of an event-driven architecture and aspect-oriented methods. The targeted problems are the lack of design-time adaptability, lack of testability for composition correctness, lack of behavioral features, and lack of runtime adaptability.…”
Section: A Aspect-oriented Methodsmentioning
confidence: 99%
“…The use of the AOCE methodology to build our web services-based travel planner system resulted in increased understanding of the interrelationships between the various subsystems and components concerned [4], [10], [22]. Capturing cross-cutting concerns using AOCE for the travel planner services we found that the development process was considerably simplified.…”
Section: Discussionmentioning
confidence: 99%
“…Our novel AOWS architecture enabled us to achieve a higher level of characterization and modularization in our travel planner system than other conventional approaches [22], [23]. The use of the AOCE methodology to build our web services-based travel planner system resulted in increased understanding of the interrelationships between the various subsystems and components concerned [4], [10], [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second aspect of dynamic composition is the coordination of different web services [18]. The mainstream approach is to have a single entity responsible for coordination, hence the reference to coordination as orchestration.…”
Section: Requirements For Dynamic Compositionmentioning
confidence: 99%